INCREASING ABILITY TO READ UNDERSTANDING THROUGH PQ4R METHOD IN CLASS IV STUDENTS SDI ARRAYAAHIIN BEKASI DISTRICT - Roza Kemala; Matin Matin; Yetti Supriyati (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2021)
The purpose of this study is to make improvements in the learning process and improve learning outcomes Indonesian fourth grade student at Arrayaahiin Elementary Islamic School west C ikarang Bekasi District using the PQ4R method (Preview, Question, Read, Recite, Reflect and Review.) This research was conducted in SDI Arrayaahiin Bekasi Regency. This research method is a class action research that uses a spiral or cycle model from Kemmis and Taggart. The cycle is carried out twice with four rounds of each cycle, namely planning, implementation, action, observation and reflection. That is, in the first cycle, the percentage of reading comprehension reached 67%, with a teacher observation size of 93%. In the second cycle, the percentage of reading comprehension reached 80%, and observation measured 94% of teachers. Once discovered, there is a gradual increase in learning after the action. The PQ4R method not only helps students in the skills expected in the learning process at school. However, it is very important to equip students with a systematic learning method. The method of use for the benefit of the studio will produce supported understanding, not memory. Understanding that discuss relative will last longer in the brain, than just remembering the facts.